Application of minimum quantity lubrication for various machining processes - A mini review - N. E. H., Zamiruddin; Nurrina, Rosli (Penerbit UMP, 2020)
Minimum Quantity Lubrication (MQL) is a great alternative lubricating and cooling environment method that has been widely used to replace the conventional flood coolant which brings drawbacks involving environmental awareness, human’s safety and health and manufacturing cost. Taking into account the recent trends, this review paper describes a summary of the research journals reviewed previously MQL in various machining operations involving milling, turning, drilling and grinding of various types of materials. Most recent papers have described the use of vegetable oils which helps in maintaining the environmentally friendly machining. Also, the aided of nanofluid particles and hybrid environment in MQL application conversed the outstanding efficiency in machining performances as compared to that conventional flood lubrication technology. Briefly, this paper have shown the proficiency of eco-friendly MQL approach in improving the performance of machinability such as reducing the surface roughness of workpiece, increase of tool life and also reducing the cutting temperature that leads to a sustainable machining environment in the future work.